Single, straight, wants kids: media framing of single, heterosexual fatherhood via assisted reproduction. Issue 4 (4th July 2017) - Johnson, Katherine M.
Abstract: The new reproductive technologies have made possible various postmodern family forms. I highlight an emerging form that has received little attention: single fathers by choice (SFCs), created by single men using egg donation and surrogacy. I focus on heterosexual SFCs, which have been largely ignored in the scholarly literature even as gay and lesbian parenthood have increasingly become topics of feminist inquiry. This type of fatherhood raises several important questions for gender and family scholars about the 'traditional' family, the relationship between masculinity and fatherhood, and men's own desires for parenthood without a female partner. I analyze US media framing to explore cultural sense-making of SFCs. While media framing cannot tell us about men's lived experiences as intentional single fathers, it does point to larger discourses that potentially impact these men as they engage in non-normative fathering. I identify three core themes within the media frames: (1) viewing men and women as similar, but ultimately different, (2) addressing the tension between bachelorhood and fatherhood, and (3) representing the gender of paternal desire in multiple, conflicting ways. Overall, I argue that further investigations of SFCs can illuminate issues about men's desires for children and agency in becoming fathers.